Purifying the Nation: Population Exchange and Ethnic Cleansing in Nazi-Allied Romania, Vladimir Solonari (Baltimore: The Johns Hopkins University Press/Washington, DC: Woodrow Wilson Center Press, 2010), 451 pp., hardback 65.00 - Sherwood, Peter (Holocaust and genocide studies, 2012)
The provocative thesis of this innovative and fascinating work is that the persecution of the Jews and the Roma in Romania was not—as frequently asserted by nationalist historians—a response to pressure from Romania's ally Germany, but rather the manifestation of a distinctive, long-standing vision of an ethnically pure Romania. During the 1950s and 1960s the Communist regime maintained near-complete silence on the Holocaust, while the period of nationalistic Communism that followed permitted Holocaust-minimizing and even -denying discourse. This discourse began to change in postcommunist Romania, primarily as a by-product of accession to NATO and the EU.